EVALUASI KINERJA JALAN SEBAGAI DASAR REKOMENDASI PRIORITAS PEMBANGUNAN DALAM UPAYA PEMERATAAN PEMBANGUNAN WILAYAH KOTA SAMARINDA - Sakila Herfiana Silmy Adani; Ulwiyah Wahdah Mufassirin Liana (Racic : Rab Construction Research, 2026)
Samarinda City, as a buffer city for the Nusantara Capital City (IKN) due to its adjacent location, continues to improve urban infrastructure such as providing and repairing pedestrian paths. However, there are still many road sections without pedestrian facilities, such as on Jl. Wahid Hasyim II, Jl. Pangeran Suryanata, and Jl. Pangeran Antasari. This research conducted a review of the performance and side friction class of road segments using the PKJI method, resulting in Jalan Wahid Hasim II with a Saturation Degree of 0.63 (LOS C) and a side friction value of 315.9 smp/hour, Jalan Pangeran Suryanata with a Saturation Degree of 1.06 (LOS F) and a side friction value of 274.7 smp/hour, and Jalan Pangeran Antasari with a Saturation Degree of 0.82 (LOS E) and a side friction value of 357.1 smp/hour. This research is expected to serve as a recommendation for the government in prioritizing the development and improvement of road performance in providing pedestrian facilities to reduce congestion and conflicts among road users, as well as to ensure comfort and safety for pedestrians.